2020
DOI: 10.1002/aoc.5515
|View full text |Cite
|
Sign up to set email alerts
|

Direct oxidative C(sp3)─H/C(sp2)─H coupling reaction using recyclable Sr‐doped LaCoO3 perovskite catalyst

Abstract: A strontium‐doped lanthanum cobaltite perovskite, La0.6Sr0.4CoO3, was prepared and utilized as a recyclable heterogeneous catalyst for the direct oxidative C(sp3)─H/C(sp2)─H coupling reaction between cyclic ethers and alkenes or coumarins to achieve corresponding α‐functionalized ethers. The α‐functionalization of cyclic thioethers or amides with alkenes or coumarins was also achieved via this protocol. The La0.6Sr0.4CoO3 catalyst exhibited better performance than a variety of homogeneous and heterogeneous cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Correspondingly, the reaction carried out at 100 and 120 • C gave significantly higher product yields of 37% and 67%, respectively. However, no further enhancement in the formation of the major product was observed when increasing the reaction temperature to 140 • C. Indeed, the dehydrogenative alkenylations of ethers catalyzed by molecular Cu salts were performed at 120 • C in the earlier studies, implying that this temperature condition was not only appropriate for selective activation and coupling of C(sp 2 )-H and C(sp 3 )-H bonds but also controlled the unexpected oxidation of alkene substrates in the presence of the DTBP oxidant [13,15,80,81]. In the work on oxidative coupling, Trinh and co-workers also reported that the oxidation of 1,1-diphenylethylene to benzophenone by DTBP was significant at 140 • C [82].…”
Section: Catalytic Study 221 Optimization Of Reaction Conditionsmentioning
confidence: 94%
See 2 more Smart Citations
“…Correspondingly, the reaction carried out at 100 and 120 • C gave significantly higher product yields of 37% and 67%, respectively. However, no further enhancement in the formation of the major product was observed when increasing the reaction temperature to 140 • C. Indeed, the dehydrogenative alkenylations of ethers catalyzed by molecular Cu salts were performed at 120 • C in the earlier studies, implying that this temperature condition was not only appropriate for selective activation and coupling of C(sp 2 )-H and C(sp 3 )-H bonds but also controlled the unexpected oxidation of alkene substrates in the presence of the DTBP oxidant [13,15,80,81]. In the work on oxidative coupling, Trinh and co-workers also reported that the oxidation of 1,1-diphenylethylene to benzophenone by DTBP was significant at 140 • C [82].…”
Section: Catalytic Study 221 Optimization Of Reaction Conditionsmentioning
confidence: 94%
“…The major product could be achieved in the presence of either Ce or Cucontaining materials, confirming that both Ce and Cu species are responsible for the selective cross-dehydrogenative coupling between 1,1-diphenylethylene and THF (Table 3). According to the previous studies, a plausible redox cycle for the direct alkenylation of THF with 1,1-diphenylethylene catalyzed by the Cu 1 Ce 0.7 Si catalyst was proposed (Figure 13) [12,13,15,78,83,84]. First, decomposition of DTBP into tert-butoxy radicals is accelerated at high temperatures in the presence of transition metal species [12,77,79,84].…”
Section: Comparison Of Catalystsmentioning
confidence: 97%
See 1 more Smart Citation